Redefinition of the cicada tribe Hemidictyini Distant, 1905, status of the tribe Iruanini Boulard, 1993 rev. stat., and the establishment of Hovanini n. tribe and Sapantangini n. tribe (Hemiptera: Cicadidae) - Sanborn, Allen F.; Marshall, David C.; Moulds, Maxwell S.; Puissant, Stéphane; Simon, Chris (Zootaxa, 2020)
A recent paper by Ruschel & Campos (2019) on “leaf-winged” cicadas proposed a significant reorganization of the cicada tribe Hemidictyini Distant, 1905g, including synonymization of the monogeneric tribe Lacetasini Moulds & Marshall, 2018 following the results of a cladistic parsimony analysis of morphological characters. In this study, we reconsider and revise the morphological analysis of Ruschel & Campos and obtain new genetic data for Hemidictya. We find that their study suffers from a limited taxon sample, inappropriate outgroup selection, and misinterpretation of genitalic characters (uncus vs. claspers). We show that Hemidictyini sensu Ruschel & Campos includes members of multiple tribes and subfamilies, and we conclude that some of the taxonomic transfers by Ruschel & Campos are not supported. The two most similar and leaf-like cicadas, Hemidictya Burmeister, 1835 (South America) and Hovana Distant, 1905g (Madagascar), are probably not closely related but rather an excellent example of convergent evolution. Lacetasini is not a junior synonym of the Hemidictyini but a distinct part of the Tettigomyiinae Distant, 1905g as originally classified. We return or transfer the genera Lacetas Karsch, 1890, Iruana Distant, 1905g, Bafutalna Boulard, 1993, and Murphyalna Boulard, 2012 to the Lacetasini. With the transfer of all genera of Iruanina Boulard, 1993 and Bafutalnina Boulard, 1993 to Lacetasini and with Lacetas transferred to the Iruanina, Lacetasini n. syn. becomes a subjective junior synonym of Iruanini rev. stat. in the Tettigomyiinae. We assign Hovana to Hovanini n. tribe in the Tettigomyiinae and Sapantanga Distant, 1905g to Sapantangini n. tribe in the Tibicininae Distant, 1905b. We propose that Hemidictyini sensu novo contains only the genus Hemidictya and we assign the tribe to Tibicininae with a revised diagnosis.